A relação entre educação e serviço social: breve análise dos desafios e possibilidades emergentes deste encontro - Irassochio, Israel (My University, 2025)
This Bachelor's Thesis (TCC) in Social Work speaks about the relationship between education and Social Work. The research problem raised is: How has the relationship between Social Work and education evolved throughout history, and what are the challenges and possibilities arising from it? The aim is to understand the relationship between Social Work and education at different historical moments, as well as the challenges and possibilities resulting from its insertion into this socio-occupational space. To achieve this, critical social theory was used through the dialectical critical method, with an emphasis on the categories of historicity, totality, and contradiction. In the results and discussions, the goal was initially to identify the historical periods that shaped educational policy and the insertion of Social Work into this process. The intersection of Social Work and education is not recent; since the 1940s, schools have emerged as spaces for social workers' engagement, in response to social, economic, and political transformations. The work of social workers in education is marked by the ongoing struggle for the right to education, and the school, being one of the spaces where the various manifestations of the social issue occur, is undoubtedly one of the privileged workspaces for social workers. The current challenges and possibilities highlighted are: consolidating Law 13.935/2019, which guarantees the presence of social workers and psychologists in schools; making visible the expressions of the social issue; overcoming conservative concepts and practices; mobilizing and ensuring intersectoral work. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso (TCC) em Serviço Social versa sobre a relação entre educação e Serviço Social. A questão colocada como problemática de pesquisa é: Como se estabeleceu a relação entre Serviço Social e educação ao longo da história e quais os desafios e as possibilidades decorrentes? E objetiva compreender a relação entre Serviço Social e educação em diferentes momentos históricos e os desafios e possibilidades decorrentes da sua inserção neste espaço sócio ocupacional. Para tanto, utilizou-se a teoria social crítica por meio do método dialético crítico, com destaque nas categorias historicidade, totalidade e contradição. Nos resultados e discussões, inicialmente, buscou-se identificar os períodos históricos que estruturaram a política educacional e a inserção do Serviço Social nesse processo. O encontro do Serviço Social com a educação não é recente, desde a década de 1940, as escolas surgem como espaços de atuação para os/as assistentes sociais, em resposta a transformações sociais, econômicas e políticas. O trabalho do/a assistente social na educação é marcado pela incessante luta pelo direito à educação e, a escola, por ser um dos espaços de manifestação das diferentes expressões da questão social é, sem dúvida, um dos espaços privilegiados de trabalho dos/as assistentes sociais. Evidencia-se como desafios e possibilidades no contexto atual: consolidar a Lei 13.935/2019, que garante a presença de assistentes sociais e psicólogos nas escolas; dar visibilidade às expressões da questão social; superar concepções e práticas conservadoras; mobilizar e efetivar o trabalho intersetorial. [resumo fornecido pelo autor]
Keywords: Serviço social; Educação; Assistentes sociais; Serviço social escolar